Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Cumulative Review: 11

Answer

Answer (a): $\frac{1}{2}$ Answer (b): $9$

Work Step by Step

Part (a): We substitute $x=2$ and $y=-5$ into the expression $\frac{x-y}{12+x}$. The expression becomes $\frac{2-(-5)}{12+2}$. Simplifying, we get $\frac{2-(-5)}{12+2}$=$\frac{2+5}{14}$=$\frac{7}{14}$=$\frac{1}{2}$ Part (b): We substitute $x=2$ and $y=-5$ into the expression $x^{2}-y$. The expression becomes $2^{2}-(-5)=4+5=9$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.